A Review of Various Techniques for Removal of Fluoride from Water - Sanket Kalamkar, Anuja Kalambe, Mrunali Doye, Nikita Shende (International Journal of Modern Agriculture, 2021)
Water is one of the most important elements for all forms of life. Pure water is scarce and is not easily available at all. There are many resources which contaminates the water and one such contaminant is fluoride. Smaller amount of fluoride is beneficial for human beings, but excess amount of fluoride intake causes fluorosis such as dental fluorosis, bone fluorosis etc. and adverse effect on IQ of child. According to IS 10500-2012 the permissible limit of fluoride is 1.0 – 1.5 mg/litre and detection range is given by IS 14543 –2016 (0.05 – 1.0 mg/litre). This review article aims at different techniques used for removal of fluoride from water. These techniques include coagulation – precipitation, membrane separation process, ion exchange, adsorption techniques and so on. Among all these techniques adsorption techniques are more efficient. Now – a –days, bio-sorption method is very effective and include low-cost adsorbents such as rice husk, bone char, fruit peels and so on. This paper discusses various defluoridation techniques used in India.